2012
DOI: 10.1146/annurev-environ-042911-093511
|View full text |Cite
|
Sign up to set email alerts
|

Global Biodiversity Change: The Bad, the Good, and the Unknown

Abstract: Global biodiversity change is one of the most pressing environmental issues of our time. Here, we review current scientific knowledge on global biodiversity change and identify the main knowledge gaps. We discuss two components of biodiversity change-biodiversity alterations and biodiversity loss-across four dimensions of biodiversity: species extinctions, species abundances, species distributions, and genetic diversity. We briefly review the impacts that modern humans and their ancestors have had on biodivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
431
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(491 citation statements)
references
References 133 publications
(186 reference statements)
6
431
1
11
Order By: Relevance
“…Although numerous existing systems were identified, developing and funding them is needed to achieve global targets. Acknowledging the lack (Pereira et al 2012) and envisaging the development of a global harmonized system to observe biodiversity (Scholes et al 2012), a set of candidate EBVs were suggested (Pereira et al 2013). They aim at defining a minimum set of essential measurements and acting as an intermediate layer between primary observations (e.g.…”
Section: Earth Observation For Biodiversity Monitoringmentioning
confidence: 99%
“…Although numerous existing systems were identified, developing and funding them is needed to achieve global targets. Acknowledging the lack (Pereira et al 2012) and envisaging the development of a global harmonized system to observe biodiversity (Scholes et al 2012), a set of candidate EBVs were suggested (Pereira et al 2013). They aim at defining a minimum set of essential measurements and acting as an intermediate layer between primary observations (e.g.…”
Section: Earth Observation For Biodiversity Monitoringmentioning
confidence: 99%
“…Unfortunately, the number of species threatened with extinction far outstrips available resources for their conservation (Mace et al, 2010). This situation appears to be deteriorating rapidly, as continued environmental degradation owing to anthropogenic factors (e.g., rapid growth of the human population and overuse of natural resources) is expected to exacerbate the threats to biodiversity (Mace et al, 2010;Pereira et al, 2012). It has been suggested that more than 99% of recent species extinctions can be attributed to human activities (Mace et al, 2010;Primack and Ma, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…With a primary goal of minimizing the extinction rates of threatened species, the central theme of conservation biology is to understand the processes driving species to extinction and thereby to elucidate the requirements for species persistence (Primack and Ma, 2009). Despite the imperative to protect species threatened by human impacts, detailed data on threatened species are often unavailable to guide their management, and there also may be limited resources available to collect additional data (Mace et al, 2010;Pereira et al, 2012). However, it is unreasonable to delay risk assessment for a given species until there are sufficient data, as conservation decisions must be made swiftly and can therefore use only the best information at hand (Brook et al, 2002;Tian et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…If global temperature or atmospheric CO 2 concentrations, for example, are increasing at the global scale, the net change over time within local areas must, on average, be positive. However, because local species losses may be accompanied by immigration of species from elsewhere, decreases in biodiversity at the global scale do not necessarily result in any biodiversity change at smaller scales (16,19,20). Here we present a global synthesis testing for directional changes in local-scale biodiversity of terrestrial plants, which have been the focus of most well-replicated biodiversity-ecosystem function (BDEF) experiments.…”
mentioning
confidence: 99%